2008
DOI: 10.1093/cercor/bhn100
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences and the Impact of Steroid Hormones on the Developing Human Brain

Abstract: Little is known about the hormonal effects of puberty on the anatomy of the developing human brain. In a voxel-based morphometry study, sex-related differences in gray matter (GM) volume were examined in 46 subjects aged 8-15 years. Males had larger GM volumes in the left amygdala, whereas females had larger right striatal and bilateral hippocampal GM volumes than males. Sexually dimorphic areas were related to Tanner stages (TS) of pubertal development and to circulating level of steroid hormones in a subsamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
283
4
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(326 citation statements)
references
References 70 publications
22
283
4
8
Order By: Relevance
“…To date, attempts to relate testosterone signaling to brain anatomy in humans have relied on interindividual differences in serum testosterone levels (that are hard to acquire with high reliability; ref. 19), and used crosssectional study designs that have factored out the effects of age (20,22) and/or sex (21). Therefore, our focus on genetically determined variation in androgen receptor functioning within a longitudinal study of adolescent cortical thickness change provides some of the strongest evidence to date that androgen signaling has the capacity to influence neurodevelopmental processes in humans.…”
Section: Genetic Variation Conferring Enhanced Androgen Receptor Effimentioning
confidence: 99%
See 1 more Smart Citation
“…To date, attempts to relate testosterone signaling to brain anatomy in humans have relied on interindividual differences in serum testosterone levels (that are hard to acquire with high reliability; ref. 19), and used crosssectional study designs that have factored out the effects of age (20,22) and/or sex (21). Therefore, our focus on genetically determined variation in androgen receptor functioning within a longitudinal study of adolescent cortical thickness change provides some of the strongest evidence to date that androgen signaling has the capacity to influence neurodevelopmental processes in humans.…”
Section: Genetic Variation Conferring Enhanced Androgen Receptor Effimentioning
confidence: 99%
“…This lack of knowledge is partly a result of the absence of any spatially detailed longitudinal characterization of what constitutes "masculinization" of cortical maturation in humans, but also reflects the challenges of accurately (19) and repeatedly measuring serum androgens in large longitudinal cohorts-especially during adolescence, when surging androgen levels make the question of androgen receptor-mediated influences on brain development highly relevant. The few studies that have attempted to relate circulating androgens to brain anatomy in humans are cross-sectional in design, and have generated mixed results (20)(21)(22), although the largest of these studies report that possession of a genetic variant conferring more efficient androgen receptor functioning strengthens the relationship between peripheral measures of testosterone and brain anatomy (23,24).…”
mentioning
confidence: 99%
“…However, after controlling for age, pubertal testosterone has been associated with individual differences in structural brain development (Peper et al, 2011). For example, a larger amygdala and hippocampus volume are related to increased levels of testosterone in both sexes regardless of age (Neufang et al, 2009).…”
Section: Review Of Lombardo Et Almentioning
confidence: 99%
“…The secretion of testosterone is modulated indirectly by the gonadotropin-releasing hormone, which is secreted by the hypothalamus [Greenstein and Greenstein, 2000]; these two hormones are part of the same regulatory circuit of hormones [Greenstein and Greenstein, 2000]. However, VBM analyses showed that testosterone level was associated with brain structures in the amygdala [Bramen et al, 2011] and hypothalamus [Neufang et al, 2009] in children, and in these studies, positive associations were observed between rGMV and the testosterone level in these areas. However, the associations between testosterone level and white matter structures or such associations in young adults who showed maturation remain unclear.…”
Section: Discussionmentioning
confidence: 99%